2019
DOI: 10.1080/1369183x.2018.1547022
|View full text |Cite
|
Sign up to set email alerts
|

Parental migration and disruptions in everyday life: reactions of left-behind children in Southeast Asia

Abstract: Increasing feminisation of transnational labour migration has raised concerns over potential ‘care crises’ at home, and consequently a ‘care deficit’ for children left in origin countries. Our paper focuses on how left-behind children from Indonesia and the Philippines understand, engage and react to changes in their everyday lives in their parents’ absence. While many children had no say over their care arrangements, some were able to assert their agency in influencing their parents’ decisions and eventually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 30 publications
3
68
0
1
Order By: Relevance
“…Such situations can emotionally disturb 'left-behind' children and create poignant consequences for child and family welfare (Lam and Yeoh, 2019). Women's migration decisions are generally premised on improving the long-term life chances of their children to gain a good education and well-paid occupation.…”
Section: Transnational Family Care Regimesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such situations can emotionally disturb 'left-behind' children and create poignant consequences for child and family welfare (Lam and Yeoh, 2019). Women's migration decisions are generally premised on improving the long-term life chances of their children to gain a good education and well-paid occupation.…”
Section: Transnational Family Care Regimesmentioning
confidence: 99%
“…Thus, both mothers and fathers face a migration paradox in which migration takes place for the purpose of improving children's economic welfare, but is often at the cost of children's emotional well-being (Lam and Yeoh, 2019). Furthermore, as parents separated from their children, both women and men experience extreme loneliness and alienation.…”
Section: Transnational Family Care Regimesmentioning
confidence: 99%
“…Second, our study adds to a new strand of literature that adopts a more children-inclusive approach (Choi, Yeoh, & Lam, 2018; to investigate the effects of parental migration on children's outcomes (see Section 2.1). To cope with parental absence and new family configuration, left-behind children may build skills and strategies and actively demonstrate agency in determining migration outcomes (Asis, 2006;Lam & Yeoh, 2019). In this study, we therefore rely on self-reported outcomes of school children in the age group aged 11-15 and not on children's assessments performed by adults.…”
Section: Introductionmentioning
confidence: 99%
“…As for the child generation, within the context of transnational families, the major focus is on their transnational care arrangement (Battistella and Conaco 1998;Best 2014). This focus is embedded into four specific research areas around the child generation(s) of immigrants, including the left-behind children in situ (Graham et al 2012;Lam and Yeoh 2019), the children in the astronaut family (Waters 2002(Waters , 2005, the parachute kid (Zhou 1998), and the transnational engagement of immigrant child generations (Wolf 2002;Bartley and Spoonley 2008). Both the 1.5 and second generations of immigrant children have constituted a major cohort for scholarly investigations.…”
Section: Transnational Immigrant Families -A Brief Literature Reviewmentioning
confidence: 99%